Redes interorganizacionais na conformação de políticas públicas: o caso "Minas Biotec" - Machado, Ingrid Lamounier (2016)
This research is guided by the search for understanding of the functioning of inter-organizational networks in in shaping public policy. It was decided, in this dissertation, the study of inter-organizational networks directed to the field of innovation. This approach also considers as analytical approach the actions based on the principle of Triple Helix (ETZKOWITZ, 2011). For this study, it was decided as analyzed in the Innovation System of Minas Gerais, and as observation unit, the "Minas Biotec." The question that guided the analysis was: how is the operation of Interorganizational Network Innovation System of Minas Gerais? It attempted to thus understand the mechanisms by which institutions are organized, cooperate and interact to provide innovation policy through the network. This question originated from the general objective of this work, which was to verify the operation of the network level Innovation System of Minas Gerais under the institutional point of view. This overall objective has been divided into three specific objectives: describe the overall environment, specific and technical Innovation System of Minas Gerais; identify the governance of the "subnet" "Minas Biotec", outlining its emergence, its key players and functions in the network; and analyze the institutional functioning of the Innovation System of Minas Gerais through the study of the "Minas Biotec" from 2006 to 2014. In terms of methodology, the procedures adopted were qualitative and used as empirical strategy case study "Minas Biotec" The analysis variables were extracted and adapted from Leite (2011). The results of the analysis indicated that the operation of the Innovation System of Minas Gerais is permeated by interorganizational dynamics strongly influenced by institutional elements that induce the behavior of organizations and affected the shaping of innovation policy. It was found the importance of political leadership in the conduct of actions and the centrality of SECTES in the governance of "Minas Biotec ", and his performance was decisive for coordination between the actors of the network and the achievement of results. The analysis of the "Minas Biotec”, also revealed the presence of coercive isomorphic mechanisms, normative and mimetic in the relationship of the actors (DIMAGGIO; POWELL, 1983), and the search for legitimacy, resulting in myths and ceremonies (MEYER; ROWAN, 1977), Finally, the challenges are points that are related to inter-organizational dialogue that permeates the triple helix.